A New Surgical Approach for the Management of Acute Corneal Hydrops Complicated With Corneal Perforation. Issue 8 (August 2020) - Petrelli, Myrsini; Cohen, Judith; Hashemi, Kattayoon; Grentzelos, Michael A.; Kymionis, George D.
Abstract : Purpose: To report an unusual case of a patient with keratoconus and acute hydrops complicated with corneal perforation and describe its management using a new surgical approach. Methods: A case report and new surgical approach description. Results: A 47-year-old female patient with a history of keratoconus and implantable contact lens surgery presented at our institute with symptoms of acute corneal hydrops in her right eye. On examination, best corrected visual acuity was of counting fingers in the involved eye. Slit-lamp examination revealed a small inferotemporal corneal perforation, surrounded by marked corneal edema and a positive Seidel test. Initial attempts of conservative treatment with cyanoacrylate tissue adhesive application and bandage soft contact lens placement were ineffective. We decided to proceed with an inferior, lamellar wedge resection of the diseased corneal tissue. One month postoperatively, the cornea remained clear, whereas best corrected visual acuity was 0.1. Conclusions: Lamellar wedge resection could represent an alternative surgical approach for keratoconic patients, with eccentric acute hydrops and subsequent corneal perforation that provides rapid visual rehabilitation. Abstract : Supplemental Digital Content is Available in the Text.